Respuesta :

For this case we must find the zeros of the following function:

[tex]f (x) = (x-7) (x-3) (x-2)[/tex]

If we equate each term to 0 and we clear the variable "x", we will find the values that make the function equal to zero. So:

  • [tex]x-7 = 0\\x = 7[/tex]
  • [tex]x-3 = 0\\x = 3[/tex]
  • [tex]x-2 = 0\\x = 2[/tex]

Thus, the zeros of the function are:

7,3,2

Answer:

Option C

The zeros of the function f(x) = (x - 7)(x - 3)(x - 2) are 7, 3, 2. The correct option is the third option 7, 3, 2

From the question,

We are to determine the zeros of the given function

The given function is

f(x) = (x - 7)(x - 3)(x - 2)

To determine the zeros of this function, we will set f(x) = 0

That is ,

f(x) = (x - 7)(x - 3)(x - 2)  becomes

0 = (x - 7)(x - 3)(x - 2)

∴ (x - 7)(x - 3)(x - 2) = 0

Then,

We can write that

x -7 = 0 OR x - 3 = 0 OR x - 2 = 0

∴ x = 7    OR    x = 3    OR   x = 2

Hence, the zeros of the function f(x) = (x - 7)(x - 3)(x - 2) are 7, 3, 2. The correct option is the third option 7, 3, 2

Learn more here: https://brainly.com/question/12488960